A Precise Computer Model for Real Estate Assessment - Dasso, Aristides (2013)
Real Estate Assessment –or Appraisal– is mainly employed in government for taxation purposes. There are a number of methodologies to assess the value of a property so as to calculate taxes or just its value. Normally, several attributes belonging to the property are used for this purpose, and one of the most simple method employed it is the additive method. Among the attributes used, it can be found the plot area, the area of the buildings, the improvements on the property, the intended use (e.g. production, habitation, etc.), geographical location, etc. This assessment can be used as a percentage, index, proportion, etc. to levy the taxes. There are different kinds of property tax, e.g. ad valorem, special tax, etc. We propose here the use of a general method that can be used with any of these. This method –the Logic Score of Preference (LSP) method– provides a way to aggregate different attributes of a property into a single value using a Continuous Logic. The resulting index can then be used to calculate the final value of the tax. The method is flexible and it allows a wide range of possibilities as well as a fine gradation of the value of different properties; it also allows to contemplate the varied conditions and attributes of properties to make a more precise assessment.